2005
DOI: 10.1074/jbc.m409580200
|View full text |Cite
|
Sign up to set email alerts
|

Nur77 Regulates Lipolysis in Skeletal Muscle Cells

Abstract: Skeletal muscle is a major mass peripheral tissue that accounts for ϳ40% of total body weight and 50% of energy expenditure and is a primary site of glucose disposal and fatty acid oxidation. Consequently, muscle has a significant role in insulin sensitivity, obesity, and the blood-lipid profile. Excessive caloric intake is sensed by the brain and induces ␤-adrenergic receptor (␤-AR)-mediated adaptive thermogenesis. ␤-AR null mice develop severe obesity on a high fat diet. However, the target gene(s), target t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(64 citation statements)
references
References 62 publications
3
60
0
1
Order By: Relevance
“…Fatty Acid Oxidation Assay- [9, H]Palmitic acid was used as a substrate, and palmitic acid oxidation was assessed by measuring 3 H 2 O produced in the cell culture medium as described previously (14). Briefly, LS-174T or HCT-116 cells were seeded at 1.3 ϫ 10 5 cells/well in a 12-well plate.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Fatty Acid Oxidation Assay- [9, H]Palmitic acid was used as a substrate, and palmitic acid oxidation was assessed by measuring 3 H 2 O produced in the cell culture medium as described previously (14). Briefly, LS-174T or HCT-116 cells were seeded at 1.3 ϫ 10 5 cells/well in a 12-well plate.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…The aqueous phase containing 3 H 2 O was collected and subjected to liquid scintillation counting. For the PGE 2 treatment assay, cells were serum-starved for 48 h, and PGE 2 (1 mol/liter) was added for 2 h before the addition of [9, H]palmitic acid.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Then we examined the expression of some inhibitory proteins for SREBP1, including AMRK and ATF6, but none of them was positively correlated with NR4A1 expression (data not shown). As p53 was also reported as an inhibitory protein for SREBP1c expression,30 we therefore checked the expression of p53. Our data showed that the expression of p53 at both protein (Figure 7B) and mRNA levels (Figure 7C) in adipose tissues of KO mice was reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we found that NR4A1 overexpression inhibited adipogenesis in 3T3‐L1 pre‐adipocytes. In vivo, it has been reported that NR4A1 had the effects on glucose and lipid metabolism in liver 31, 32 and muscles 30, 33. Studies have shown that NR4A1 knockout mice fed with high‐fat diet were more likely to develop obesity compared to WT mice 23.…”
Section: Discussionmentioning
confidence: 99%